Klasifikasi Ilmu Menurut al-Farabi dan Relevansinya terhadap Perkembangan Keilmuan Kontemporer - Fathurrahman. Mh, A.; Khudori Soleh, Achmad; Asy-Syarifah, Chodijah; Tanjung, Wahyuditira (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The classification of knowledge formulated by al-Farabi remains highly relevant to the development of contemporary sciences, particularly in integrating rational and revealed knowledge. This study aims to analyze the relevance of al-Farabi’s classification of sciences to modern scientific paradigms. The research employs a qualitative method with a library research approach and philosophical analysis, focusing on al-Farabi’s works and contemporary interpretations of his thought. The findings indicate that al-Farabi divides knowledge into two major categories: theoretical sciences, which emphasize the development of fundamental concepts and principles, and practical sciences, which focus on the application of knowledge in social and ethical contexts. This classification aligns with the modern structure of scientific disciplines encompassing the natural sciences, humanities, and social sciences. The study concludes that al-Farabi’s epistemological framework is not merely historical but provides a foundational and integrative model for the development of contemporary science that harmonizes rational, ethical, and spiritual dimensions.